Probing the molecular interactions of electrochemically reduced vitamin B2 with CO2 - Tonanon, Panyawut (2025)
The electrochemical reduction of riboflavin (vitamin B2) in a dimethyl sulfoxide solvent was examined under a CO2 atmosphere and compared with results under an argon atmosphere. Variable-scan-rate cyclic voltammetry combined with controlled potential electrolysis (CPE) and analysis by UV-vis and EPR spectroscopies provided insights into the nature of interactions of reduced flavins with dissolved CO2. Reductive exhaustive CPE experiments under CO2 indicated an overall two-electron stoichiometry, compared to one-electron reduction under an argon atmosphere, due to the lowering of the formal one-electron reduction potential of the flavin radical anion to form the dianion, which can be rationalized by riboflavin-CO2 molecular interactions. UV-vis spectroscopic measurements confirmed complete chemical reversibility of the redox transformations over extended time scales. Digital simulation modeling of the voltammetric data enabled extraction of thermodynamic and kinetic parameters for the proposed mechanism, comprising multiple proton-coupled electron transfer steps, diamagnetic anions, radical anions, and neutral radical intermediates enroute to the fully reduced state, as well as evidence of a long-lived solution phase complex of the reduced riboflavin with CO2.